2022
DOI: 10.1109/tnsre.2022.3154891
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Deep Neural Network for Automatic Classification of EEG Independent Components

Abstract: Objective: Independent component analysis (ICA) is commonly used to remove noisy artifacts from multi-channel scalp electroencephalogram (EEG) signals. ICA decomposes EEG into different independent components (ICs) and then, experts remove the noisy ones. This process is highly time-consuming and experts are not always available. To surpass this drawback, research is going on to develop models to automatically conduct IC classification. Current state-of-the-art models use power spectrum densities (PSDs) and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…One important step is to remove artefacts naturally occurring in the non-controlled environment of presurgical monitoring. This step was performed using the algorithm developed by Lopes et al 33 described below. First, the scalp EEG signals were filtered using a 0.5–100 Hz bandpass 4th-order Butterworth filter and a 50 Hz 2nd-order notch filter.…”
Section: Methodsmentioning
confidence: 99%
“…One important step is to remove artefacts naturally occurring in the non-controlled environment of presurgical monitoring. This step was performed using the algorithm developed by Lopes et al 33 described below. First, the scalp EEG signals were filtered using a 0.5–100 Hz bandpass 4th-order Butterworth filter and a 50 Hz 2nd-order notch filter.…”
Section: Methodsmentioning
confidence: 99%
“…Although this process usually performs well in removing noise from EEG signals, it requires visual inspection of data, making it difficult when experts are not available. Consequently, several researchers have developed classifiers to automatically perform this task 12 , 16 27 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Training set contains 43,038 (70.44%) brain ICs and 18,054 (29.56%) artifact ICs whereas testing set contains 11,437 (70.02%) brain ICs and 4,897 (29.98%) artifact ICs. These data were already used in a previous study 27 . In that study, authors concluded that using the three sources of information improved the IC classifiers’ performance.…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…One important step is to remove artifacts naturally occurring in the non-controlled environment of presurgical monitoring. This step was performed using the algorithm developed by Lopes et al 33 . First, the scalp EEG signals were filtered using a 0.5-100 Hz bandpass 4th-order Butterworth filter and a 50 Hz 2nd-order notch filter.…”
Section: Eeg Signal Preprocessingmentioning
confidence: 99%